(untitled) (American Journal of Food Science and Technology, 2024)
The increasing demand for turkey as a protein source necessitates effective management practices, particularly in combating Salmonella infections. This study evaluated the immune response of four turkey strains (black, white, exotic, and lavender) to a Salmonella gallinarum-9R strain vaccine. A total of 180 samples of day-old poults (45 from each strain) were used for the experiment. Following initial blood sampling at four weeks, all birds were vaccinated orally with the Salmonella vaccine. Monthly blood samples were collected over four months to assess antibody titres using a serial dilution method. Results revealed significant differences in the mean antibody responses among the strains. The black strain exhibited the highest mean antibody titre (1.38), followed closely by the exotic (1.32) and white (1.30) strains, while the lavender strain showed the lowest titre (1.17). The antibody titres significantly increased post-vaccination compared to pre-vaccination values (p < 0.05). These findings highlight the effectiveness of vaccination in enhancing immunity in turkeys, suggesting that selective breeding of more responsive strains could improve flock health and reduce the risk of Salmonella infection.